2022
DOI: 10.1002/smi.3180
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence as a pathway from fatigue to psychological distress in mothers who are breast cancer survivors

Abstract: Fatigue is prevalent and pervasive among breast cancer survivors. Mothers are particularly susceptible to fatigue due to the ongoing demands of their caring role.While fatigue has been associated with psychological distress in prior research, the pathway by which fatigue translates into psychological distress is unclear. Given the theoretical and empirical links between fatigue, fear of cancer recurrence (FCR) and psychological distress, the role of FCR in mediating the relationship between fatigue and psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The bridge symptom “Poor spirits” and the symptom “Loss of emotional control” (E2-D1, edge weight = 0.22) ranked second in terms of closeness of connection; these symptoms belong to the “Sense of failure” and “Helplessness” dimensions, respectively. Previous research ( 38 40 ) found a strong association between physical symptoms such as fatigue and a fear of cancer recurrence among cancer survivors, as patients may misinterpret their fatigue as a sign of cancer recurrence or progression. However, fighting the disease commonly leads to fatigue, causing the patient to fear cancer recurrence and resulting in a poor mental state.…”
Section: Discussionmentioning
confidence: 99%
“…The bridge symptom “Poor spirits” and the symptom “Loss of emotional control” (E2-D1, edge weight = 0.22) ranked second in terms of closeness of connection; these symptoms belong to the “Sense of failure” and “Helplessness” dimensions, respectively. Previous research ( 38 40 ) found a strong association between physical symptoms such as fatigue and a fear of cancer recurrence among cancer survivors, as patients may misinterpret their fatigue as a sign of cancer recurrence or progression. However, fighting the disease commonly leads to fatigue, causing the patient to fear cancer recurrence and resulting in a poor mental state.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with those of various studies in the field indicating that the FCR is associated with various psychological variables and can increase the psychological distress and burden of the patients. According to a recent cross-sectional study in Australia among breast cancer survivors, the FCR had a positive correlation with anxiety, depression, stress, and fatigue among the participants [28]. Those researchers indicated that the FCR can act as a mediating factor in transitioning from fatigue to psychological distress [27].…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms are observed from the time of diagnosis and can last for more than 10 years after treatment has ended 30 . These emotional issues have been identified as the most important variables that influence the quality of life and adaptation of breast cancer patients following primary treatment 22 , 31 . Considering that the association between these emotional symptoms and long-term survival rates in cancer patients has been established 32 , emotional symptoms must be monitored continuously and comprehensive approaches for mental health promotion, such as psychological support and counseling specifically designed for breast cancer survivors, must be implemented.…”
Section: Discussionmentioning
confidence: 99%